Formation of EMT/FAU intergrowth and nanosized SOD zeolites from synthesis gel of zeolite NaX containing ethanol - Nawee Jantarit; Pimwipa Tayraukham; Nattawut Osakoo; Karin Föttinger; Jatuporn Wittayakun (Materials Research Express, 2020)
Ethanol can serve as an organic additive in zeolite synthesis due to the ease of availability and simple removal. It can influence the crystallization leading to zeolites with different phases and morphology. This study explores the effect of partial displacement of water in the synthesis gel of zeolite NaX by various amounts of ethanol. With one-pot synthesis, the gels with different ethanol/water molar ratios are crystallized 90 °C for 18 h under a static condition. The products are characterized by several techniques including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning and transmission electron microscopy (SEM and TEM), nitrogen sorption analysis, inductively coupled plasma-optical emission spectrometry (ICP-OES), and thermogravimetric analysis (TGA). The ethanol/water molar ratio of 0.045 produces EMT/FAU intergrowth with a hollow structure and undefined shapes. The ratios of 0.412 and 0.628 give the aggregates of nanocrystalline SOD zeolite. Moreover, the molar ratios of 0.101, 0.174 and 0.273 provide a mixture of the three phases. All zeolite products contain both intrinsic micropores and interparticle mesopores. The higher ethanol/water molar ratio in the gel produces the zeolites with the lower Si/Al ratio due to the higher Al incorporation in the zeolite structure. In summary, we demonstrate alternative template-free approaches to synthesize EMT/FAU intergrowth and nanosized SOD zeolite with short crystallization time and low crystallization temperature. The finding is an example of ethanol influence on the crystallization to control the phase and morphology of zeolite.